#### Answer

0

#### Work Step by Step

Given -$x^{2}$ + 9, x = 3
Now put the value of x=3 in the given expression
=-$(3)^{2}$ + 9
=-9+9
=0

Published by
Pearson

ISBN 10:
0321867327

ISBN 13:
978-0-32186-732-2

0

Given -$x^{2}$ + 9, x = 3
Now put the value of x=3 in the given expression
=-$(3)^{2}$ + 9
=-9+9
=0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.